Association between age and severity to leptospirosis in children. - Gilles Guerrier; Pauline Hie; Ann-Claire Gourinat; Emilie Huguon; Yann Polfrit; Cyrille Goarant; Eric D'Ortenzio; Isabelle Missotte (Public Library of Science (PLoS), 2013)
BACKGROUND: In endemic areas, leptospirosis is more common and more severe in adults compared with children. Reasons to explain this discrepancy remain unclear and limited data focusing on adolescents are available. The objective of the study was to describe disease spectrum and outcome differences in children and adolescents admitted for leptospirosis in a large at-risk population. METHODS: Clinical and laboratory data were obtained on hospitalized cases in New Caledonia from 2006 to 2012. RESULTS: Data of 60 patients <18 years of age (25 children under 14 and 35 adolescents aged 14 to 17) with confirmed leptospirosis were analyzed. Compared with children, adolescents presented more often with classic features of Weil disease (p = 0.02), combining hepatic and renal involvement with or without pulmonary participation. Jarisch-Herxheimer reactions were observed more often among adolescents (p<0.01). The overall case fatality rate was low (1 adolescent versus 0 children). CONCLUSION: Severe leptospirosis in adolescents may be more likely to show adults' characteristics compared with children. Further studies are required to explore age-dependant host factors, including puberty-related physiological changes.